2022
DOI: 10.1155/2022/6110228
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Middle Cerebral Artery Hemodynamic Changes and Significance under Ultrasound Detection in Hypertensive Disorder Complicating Pregnancy Patients with Different Severities

Abstract: Colour Doppler ultrasound was applied for monitoring the hemodynamic parameters of fetal uterine artery (UtA), umbilical artery (UA), and middle cerebral artery (MCA) during pregnancy. In hypertension disease complicating pregnancy, these hemodynamic measures and their therapeutic applicability value were reviewed (HDCP). 120 singleton pregnant women were chosen, with 40 cases of mild preeclampsia (mild group), 40 cases of severe preeclampsia (severe group), and 40 normal control pregnant women (control group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Lopez-Mendez et al 15 revealed a mean MCA PI of 1.47 ± 0.29, a mean MCA RI of 0.69 ± 0.06, and a mean MCA S/D ratio of 5.34 ± 0.67 in the preeclamptic group. In the study by Zhou et al, 19 blood flow parameters (PI, RI, and S/D ratio) of MCA gradually decreased in the preeclamptic group compared with the normotensive group, and all differences were significant ( P < .05). These findings align closely with the results reported in this study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Lopez-Mendez et al 15 revealed a mean MCA PI of 1.47 ± 0.29, a mean MCA RI of 0.69 ± 0.06, and a mean MCA S/D ratio of 5.34 ± 0.67 in the preeclamptic group. In the study by Zhou et al, 19 blood flow parameters (PI, RI, and S/D ratio) of MCA gradually decreased in the preeclamptic group compared with the normotensive group, and all differences were significant ( P < .05). These findings align closely with the results reported in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Lopez-Mendez et al 15 reported on 52 of 103 preeclamptic pregnancies, and the UA PI mean of the cohort was 1.31 ± 0.18, a UA RI mean of 0.77 ± 0.09, and a UA S/D ratio mean of 4.4 ± 0.54. In addition, Zhou et al 19 reported higher blood flow parameters (PI, RI, and S/D ratio) in the preeclamptic group than in the normotensive group, with all differences being significant ( P < .05). Zhou et al’s findings align well with our study findings.…”
Section: Discussionmentioning
confidence: 93%
“…Độ đặc hiệu tại điểm cắt này của chúng tôi giống với nghiên cứu của Trương Thị Linh Giang nhưng độ nhạy phát hiện bệnh thấp hơn nhiều. Pei Zhou cũng nghiên cứu trên 80 thai phụ tiền sản giật cũng tìm được điểm cắt tiên lượng kết cục bất lợi thai kỳ là 0,68 với độ nhạy cao 89,4%, nhưng độ đặc hiệu chỉ 58,7% [9]. Theo Ranjumoni Konwar (2021), giá trị của RI ĐMNG trong dự đoán kết cục chu sinh có độ nhạy 66,7%, độ đặc hiệu 70,6%, độ chính xác 68% (p = 0,01) [10].…”
Section: Giá Trị Các Chỉ Số Doppler Với Tình Trạng Thai -Giá Trị Của ...unclassified